The naturalized epistemology of legal principles - Godenzi Alegre, Jorge Luis (2018)
From its radicality the naturalized epistemology has a remarkably different perspective to the traditional epistemology, as far as the explanation, orientation and justification ofthe disciplines of the knowledge.In appealing to analytical philosophy, naturalized epistemology, applied to the juridical sciences, postulates that for the purposes of knowing some concept of law and the categories that emanate from this discipline, it is necessary to establish what are the beliefs about them Categories, one of them, that of legal principles, is to indicate their primacy and validity, on the one hand, and on the other, to determine if they coincide with what happens in their application and, therefore, if it is justified to sustain such beliefs .To reach the epistemological status of explanation and justification, these beliefs must satisfy a finite number of necessary and sufficient conditions. The necessary conditions, stipulated by the criteria used to define the notion of legal principles, are to note the meaning of the law. The belief, overwhelmingly majority, is oriented to establish that the law and the law are the same; But it could be stipulated, from a sufficient condition, to recognize that in the substrate of this discipline of knowledge, to explain, guide and justify it better, is that both law and law are totally different notions; The law is more relevant than the law because it is nourished, among other aspects, of principles that underlie the cultural fabric, constituting itself as a new type of rules that incorporate morality, with a general character and open to the legal order, , From now on, a frontal attack on traditional legal positivism.In holding this view that law is above laws, the frontiers that once separated the legal sciences from morality are blurred, since the moral relevance of the principles, which may be invoked, constitute in certain circumstances A legal duty and a new type of rules that must be observed by the operators of the right, under the same conditions as the other legal norms. Thus, the legal principles will not be different from the common laws and can be identified as such, by their content, that is to say becausethey are morally the most adequate to justify in a coherent way the set of legal rules, and also to explain the decisions Judicial, whose north must be that of the preservation of the fundamental rights guaranteeing in a minimum, legal security and social peace.This naturalized approach to epistemology may be able to solve a number of problems that have been acquired with the old traditional epistemology, such as the problem of normative statements, indeterminism of legal gaps, legal interpretation, penumbra , etc.The approach and refutation of epistemological criteria based on necessary and sufficient conditions is what stimulates this academic article that aspires to rethink new bases for the explanation and justification of the legal principles.